2021
DOI: 10.21037/apm-20-1863
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, laboratory abnormalities and CT findings of COVID-19 patients and risk factors of severe disease: a systematic review and meta-analysis

Abstract: Background: The coronavirus disease 2019 (COVID-19) is an emerging pandemic of global public health concern. We aimed to summarize the characteristics of COVID-19 patients in the early stage of the pandemic and explore the risk factors of disease progression.Methods: We conducted a systematic review with meta-analysis, searching three databases for studies published between January 1, 2020, and March 18, 2020. We used random-effects models to calculate the 95% confidence intervals of pooled estimated prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Previous works have documented that CRP might play a role in predicting a higher severity of COVID-19 in the early stages, before the development of CT findings (55). A recent systematic review and meta-analysis confirmed that elevated CRP levels are predictors of a worse prognosis in COVID-19 patients (56). Interestingly, a role on CRP values would also be determined by oral cavity health, these two variables being inversely correlated (57).…”
Section: Discussionmentioning
confidence: 94%
“…Previous works have documented that CRP might play a role in predicting a higher severity of COVID-19 in the early stages, before the development of CT findings (55). A recent systematic review and meta-analysis confirmed that elevated CRP levels are predictors of a worse prognosis in COVID-19 patients (56). Interestingly, a role on CRP values would also be determined by oral cavity health, these two variables being inversely correlated (57).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, severity of lung involvement had a negative impact on recovery, in particular a chest X-ray showing consolidation areas, PaO2/FiO2 ≤200 and high flow oxygen therapy or mechanical ventilation [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Serum ferritin level is elevated in 74.2% complicated viral infection. 63 COVID‐19 patients with elevated serum ferritin were at higher risk of developing ARDS (HR = 3.53, 95%CI: 1.52–8.16, p = 0.003). A meta‐analysis of 18 studies concluded that the ferritin level was significantly higher in severely ill patients [WMD 397.77 (95% CI 306.51–489.02)] and non‐survivors [WMD 677.17 (95% CI 391.01–963.33)].…”
Section: Hematological Changes In Severe Conditionsmentioning
confidence: 99%